Venetoclax and hypomethylating agents versus induction chemotherapy for newly diagnosed acute myeloid leukemia patients: a systematic review and meta-analysis - Yun Liu; Ying Zhang; Jinhong Gao; Lijuan Wang; Fang Xie; Chengtao Zhang; Peimin Mao; Jinsong Yan (BMC Cancer)
Abstract Background Venetoclax with hypomethylating agents (VEN-HMAs) has shown inconsistent efficacy versus induction chemotherapy (IC) in newly diagnosed AML (ND-AML). Whether or not VEN-HMAs are of clinical benefit remains uncertain. We conducted this meta-analysis to evaluate the clinical benefit of VEN-HMAs versus IC in various subtypes of ND-AML. Methods We searched PubMed, Embase, Cochrane Library, and Web of Science databases up to 17 June 2024. The quality of the included studies was assessed using the Newcastle–Ottawa Scale (NOS). Data were extracted to perform meta-analysis or descriptive analysis. The random-effects model was used to calculate the effect sizes and 95% confidence interval (CI). Relative risk (RR) was used to estimate complete response (CR), CR/ complete response with incomplete blood count recovery (CRi), overall response rate (ORR), and 30-day mortality. Hazard ratio (HR) was used to evaluate overall survival (OS) data. Results Fifteen retrospective cohort studies with 3809 participants were identified. Compared to the IC group, the pooled RR estimates for VEN-HMAs were 1.05 (95% CI 0.88–1.26, P = 0.591) for CR, 1.09 (95% CI 0.96–1.23, P = 0.195) for CR/ CRi, 0.84 (95% CI 0.60–1.18, P = 0.318) for ORR, and 0.86 (95% CI 0.50–1.49; P = 0.596) for 30-day mortality. VEN-HMAs prolonged the OS advantage in the ND-AML population (HR = 0.80, 95% CI 0.66–0.97, P = 0.025), and was demonstrated in patients with nucleophosmin 1 (NPM1) mutation (HR = 0.64, 95% CI 0.44–0.92, P = 0.017). In AML patients with RUNX1::RUNX1T1 cytogenetic abnormalities, the pooled ORR was lower in the VEN-HMAs group (RR = 0.44, 95% CI 0.28–0.69, P < 0.001), but OS was of no significantly different (HR = 1.30, 95% CI 0.52–3.26,P = 0.58). However, only 2 studies were available and the results should be taken with caution. OS benefit was similar in other subgroup analyses based on cytogenetic risk, age, and AML type (de novo, secondary, treatment-related or prior therapy for myeloid disease cohort). Conclusion Compared with the IC group, VEN-HMAs improved OS in ND-AML, especially in the NPM1 mutation subgroup (HR = 0.64), ensured the efficacy of CR, CR/CRi and ORR, without increasing 30-day mortality, necessitating further head-to-head randomized controlled trials (RCTs). Trial registration This trial was registered with PROSPERO ( www.crd.york.ac.uk/prospero/ ) on 13 July 2024, the registration number is CRD42024560585.